Naturally occurring protein nano compartments: basic structure, function, and genetic engineering. (18th October 2021) - Goel, Dimple; Sinha, Sharmistha
Abstract: Compartmentalization of reactions is the key to efficient metabolism in living organisms. Living systems have undergone several evolutionary alterations to outfit compartments that are apt to address that issues related to the slow turnover rates, competing parallel pathways and management of toxic intermediates. Several of these compartments are conditionally expressed when required, while others are permanently present in the cells. Most of these compartments in physiology have a complex makeup comprising of phospholipids, glycans and proteins. However, there are certain compartments that have a simple composition consisting of only one component. Such compartments are easy to study and explore for further in vitro applications. In this article we review the structure and function of entirely protein based natural prokaryotic and eukaryotic nanocompartments and how they have been modified or engineered to achieve a particular function in vitro.